Efektifitas Pemberian Pisang Ambon Dan Air Rebusan Jahe Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester I Di Puskesmas Tegalgede Kabupaten Garut Tahun 2025 - Sopiah, Sopi; Darmi, Salfia; Hanifa, Fanni (Innovative: Journal Of Social Science Research, 2025)
In Garut Regency in 2023, around 14.2% of 29,771 pregnant women experienced nausea and vomiting, the impact of which was a decrease in appetite. The purpose of the study was to determine the effectiveness of giving Ambon Banana and boiled ginger water on Emesis Gravidarum. The study used a quasi-experimental design with a Two Group Pretest Posttest design. The study population was pregnant women in the first trimester, with a purposive sampling technique of 30 respondents. The research instrument was a PUQE scale questionnaire. Data analysis used the Paired T-test and Independent Samples Test. The average nausea and vomiting in pregnant women before being given Ambon Banana was 9.60 after being given Ambon Banana was 6.20. The average nausea and vomiting before being given ginger water was 9.60 after being given ginger water was 6.07. The bivariate results obtained a p-value of 0.000 and the independent test obtained a p-value of 0.771. In conclusion, giving Ambon Banana and ginger water has proven to be effective and there is no difference in its effectiveness in overcoming nausea and vomiting. Suggestion: Pregnant women should increase their knowledge on how to deal with nausea and vomiting, including consuming Ambon bananas and boiled ginger water